2019
DOI: 10.1007/s40093-019-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes on soil structural stability after in natura and composted chicken manure application

Abstract: Purpose Many studies evaluate the effect of successive applications of chicken manure on soil attributes. In Brazil, the commercialization of this waste is common, implying on its sporadic use instead of many applications at the same area. The short-term effects of a single application of chicken manure and the role of its composting on soil structural stability are not fully understood. This study investigated application of in natura (uncomposted) and composted chicken manure on the structural stability of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…Carbon in soil aggregates increases their stability since it decomposes slowly or not at all (Beare et al 1994). Other authors reported the positive effect of OM on the formation of large aggregates (Šimanský et al 2008;de Melo et al 2019) and in maintaining their stability in most agricultural soils (Le Guillou et al 2011;de Melo et al 2019). Furthermore, the release of soluble salts in SWRs could help to improve soil aggregates formation and stability by promoting flocculation of clay minerals (Lakhdar et al 2010).…”
Section: Slaking Aggregate Stability and Aggregate Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon in soil aggregates increases their stability since it decomposes slowly or not at all (Beare et al 1994). Other authors reported the positive effect of OM on the formation of large aggregates (Šimanský et al 2008;de Melo et al 2019) and in maintaining their stability in most agricultural soils (Le Guillou et al 2011;de Melo et al 2019). Furthermore, the release of soluble salts in SWRs could help to improve soil aggregates formation and stability by promoting flocculation of clay minerals (Lakhdar et al 2010).…”
Section: Slaking Aggregate Stability and Aggregate Size Distributionmentioning
confidence: 99%
“…Frequent drought events due to climate change and global food demand in the coming decades urge effective actions for a more efficient use of natural resources (FAO 2015; Lee et al 2017;Wasaya et al 2018). Soil organic matter (OM) plays an important role in the regulation of soil water-dynamics by enhancing soil physical characteristics (structure, porosity, water retention, permeability) (de Melo et al 2019), and in promoting microorganisms (Williams et al 2016;Minasny and McBratney 2018;Ghosh and Devi 2019). An increase in soil organic carbon (OC) often leads to an increase in crop yield (Alagöz and Yilmaz 2009;Oguntade et al 2018;Ben Mbarek et al 2019) and can mitigate the effects of climate change by storing CO 2 in the soil (Williams et al 2016;Minasny and McBratney 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rev Bras Cienc Solo 2022;46:e0220035 These soils commonly present values of TOC higher than 20 g kg -1 in the surface layer because of their high clay content (Melo et al, 2019). Consequently, most of the dynamics caused by organic matter change in the surface layer are expected to happen in macroaggregates because free microaggregates (not aggregated into macroaggregates) are scarce (Figure 1 and Figure 3b).…”
Section: Macroaggregate Stability Evaluation In Heavy Clayey Ferralsolsmentioning
confidence: 99%
“…Por esta razón, un buen tratamiento de las camas es vital para reciclar grandes cantidades de desechos orgánicos que son una fuente importante de fertilizantes para uso agrícola (De Melo et al, 2019). En este sentido, con el fin de disminuir olores desagradables, niveles de amoniaco y carga de patógenos en las camas, son utilizados procedimientos químicos, físicos y biológicos (Kim et al, 2012;Pereira, 2016;Thomas et al, 2019).…”
Section: Manejo Y Tratamientos De La Camaunclassified